Opportunities for the development of medical education with the use of technologies. Lessons from the pandemic - Muñoz, Juan (2022)
The objective was to describe the conditions in which the classes were held once the confinement for non-essential activities was declared. A descriptive, cross-sectional methodology was used with a hermeneutic approach. A questionnaire was applied to a sample of 357 members of the Health Sciences student body of the Universidad Juárez Autónoma de Tabasco, Mexico, in May 2020. Semi-structured interviews were also conducted. In the results, it was identified that the student body had an Internet connection (87.1%), smartphones (82.5%), and a laptop (75.8%). The student body's activities were elaborating slides for presentations in class (78.8%) and reading in their textbooks (67.5%). The activities of the teaching staff were to comment at the end of the presentations (58.9%), and they requested the search for information for the elaboration of texts (61.8%). The student body mentioned that their stress levels increased (52.7%), and the tasks became more challenging to do (45.2%). The migration to virtual environments was not accompanied by changes in the structure of school activities, so it is most likely that when returning to face-to-face learning, the traditional class will be maintained.